Regulatory distance and the transfer of new environmentally sound technologies: Evidence from the automobile sector - Antoine Dechezleprêtre; Richard Perkins; Eric Neumayer (Fondazione Eni Enrico Mattei (FEEM), 2012)
This article examines the impact of environmental regulation within countries as well as regulatory distance between countries on international technology transfer. We employ a recently-assembled dataset of automobile emission standards and corresponding data on non-resident patent filing of automotive environmentally sound technologies (ESTs) in 49 countries between 1992 and 2007. Our analysis shows that an important factor shaping transfers is relative regulatory distance in that countries are more likely to receive newly-innovated technologies from source countries whose regulatory standards are closer to their own. Absolute stringency matters as well, consistent with conventional wisdom, although raising domestic environmental standards as such only leads to higher inflows of ESTs in developing countries. Novel to the literature, we show that regulatory standards in the third markets of a country's trading partners also influence transfers: countries receive more ESTs from a specific source country where they export more to markets whose regulatory standards are similar to those of the source country of the transferred technologies. As concerns both domestic regulation and regulation in a country's major export markets, it is therefore regulatory distance that matters most rather than absolute regulatory levels.
Keywords: O33; Q53; Q55; 330; Pollution Control Technologies; Environmental Regulation; International Technology Diffusion